Proximal and sensory analysis of red tilapia (Oreochromis sp.) fed with fish tanks sediments from a Biofloc culture - Delgado, Daniel Leonardo Cala [UNESP]; Rubio, Caled Alvarez [UNESP]; Quiroz, Victor Alexander Cueva [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2020)
Feeding accounts for 50%-60% of production costs in fish farming, and alternative raw materials are used to lower production costs. These raw materials can alter nutritional values ​​and sensory aspects of the final product. The present study describes the results for the proximal composition, sensory, and microbiological analyses of red tilapia (Oreochromis sp.) fed with a biofloc meal (fish sediment residue). The results showed that the red tilapia biofloc meal contained protein levels over 30%, with 3% nitrogen and 6% calcium. Fish fed biofloc meal showed productive performances within the ranges established for the species. Sensory analysis revealed that the cooked product’s appearance was very characteristic, presenting a slight metallic flavor and moderate juiciness. The bromatological composition analysis indicated that each 100g of tilapia contained 16 g of protein. Finally, the microbiological study guarantees compliance with the local tandards and confirms that the product does not contain significant levels of microorganisms that could cause foodborne diseases when consumed by humans. In conclusion, the use of biofloc meal at a small red tilapia farm proved to be a sustainable alternative for feeding Oreochromis sp.
Keywords: alternative protein; floc meal; protein feed; biofloc technology; sustainable